Dryland Maize Yield and Water‐Use Efficiency Responses to Mulching and Tillage Practices. (1st July 2017) - Zhang, Qingping; Wang, Zhennan; Miao, Fuhong; Wang, Guoliang
Abstract : Core Ideas: The highest yield and water‐use efficiency were under plastic mulching and the lowest in conventional practice. Maize yields were more sensitive to soil water at sowing under mulching and subsoiling tillage practices in the Loess Plateau. The synthesis demonstrates that ridge furrow mulching was the optimum practice for maximizing maize yield. Mulching and tillage practices is widely used to increase crop productivity and reduce water evaporation in semiarid regions. This study was conducted to determine which management practice was optimal through improving grain yield and water‐use efficiency (WUE). Based on an analysis of 44 recent publications, we synthesized maize ( Zea mays L) yield, WUE, and evapotranspiration (ET) in response to ridge furrow mulching (RFM), flat mulching (FM), straw mulching (SM), mulching with other materials (MOM), mulching with two materials combined (MTMC), rotational tillage (RT), no‐tillage (NT), and subsoiling tillage (ST) on the Loess Plateau at a broad scale. Yield ranged from 1.0 to 14.6 t ha −1, WUE from 0.30 to 5.70 kg m −3, and ET from 158 to 660 mm under mulching practices; yield ranged from 5.19 to 11.92 t ha −1, WUE from 1.45 to 3.43 kg m −3, and ET from 308 to 556 mm under tillage practices. The maximum yield and WUE were achieved under RFM (ridge and furrow mulched with plastic film) the minimum under conventional tillage (CT). Maize yield is largely related to soil water storage (SWS) at sowing under RFM, FM, SM, MOM, MTMC, and ST practices compared to NT and RT. Ridge furrow mulching and ST increased the maize yields by 58 and 9%, respectively, and corresponding for WUE by 61 and 9%. Therefore, we suggested that increasing the capture of soil water storage (SWS) at maize sowing and encouraging use of RFM practice to improve grain yield and WUE in this region.